2013
DOI: 10.1007/s11135-013-9981-7
|View full text |Cite
|
Sign up to set email alerts
|

Measuring employee perception on the effects of cultural diversity at work: development of the Benefits and Threats of Diversity Scale

Abstract: Measuring employee perception on the effects of cultural diversity at work: development of the benefits and threats of diversity scale. Hofhuis, J.; van der Zee, K.I.; Otten, S. Published in:Quality and Quantity DOI:10.1007/s11135-013-9981-7Link to publication Citation for published version (APA):Hofhuis, J., van der Zee, K. I., & Otten, S. (2015). Measuring employee perception on the effects of cultural diversity at work: development of the benefits and threats of diversity scale. Quality and Quantity, 49(1),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 55 publications
8
81
0
Order By: Relevance
“…Diversity climate, defined as an organizational climate characterized by openness and/or appreciation towards cultural differences, has emerged as one of the most promising factors determining the success of diversity management in (multicultural) organizations. Earlier studies have provided evidence that promoting a strong diversity climate may be an effective way to minimize negative outcomes, while still retaining the possibility of gaining positive outcomes of cultural diversity (Groggins and Ryan 2013 ; Hofhuis et al 2015 ). To date, however, it remains unclear which processes may be responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diversity climate, defined as an organizational climate characterized by openness and/or appreciation towards cultural differences, has emerged as one of the most promising factors determining the success of diversity management in (multicultural) organizations. Earlier studies have provided evidence that promoting a strong diversity climate may be an effective way to minimize negative outcomes, while still retaining the possibility of gaining positive outcomes of cultural diversity (Groggins and Ryan 2013 ; Hofhuis et al 2015 ). To date, however, it remains unclear which processes may be responsible for these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Cox 1993 ) or the possibility to openly discuss cultural differences between team members, as well as the problems that may arise from them (Luijters et al 2008 ). It has been shown that diversity climate opens up the possibility to actively express different viewpoints and display culturally specific behaviors (Hofhuis et al 2015 ), which in turn may increase flexibility in communication styles. Putting the two streams of research together, it is logical to assume that a strong diversity climate, in which cultural differences are encouraged and seen as valuable, is also related to more open communication between members of different cultural groups.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This study provides no evidence that diversity influences children's empathy without its influence on parent's prejudice attitudes (DE = 0.08, p = 0.49). Prior studies provided evidence that empathy can make someone perceive heterogeneity as challenges and could provide benefits (Hofhuis, Zee, & Otten, 2015). This research suggests Indonesian society to perceive the differences as opportunities.…”
Section: Resultsmentioning
confidence: 66%
“…In recent decades, the effects of diversity on team performance have been widely studied, revealing inconsistent results: depending on context and conditions, diversity may display a positive, negative or no relationship to performance (Hofhuis, van der Zee, & Otten, 2015;Van Knippenberg & Schippers, 2007;Williams & O'Reilly, 1998). The most commonly used framework for explaining the ambiguities in research findings is the Categorization-Elaboration Model (CEM; Van Knippenberg et al, 2004).…”
Section: Outcomes Of Functional Diversity In Teamsmentioning
confidence: 99%